The responsiveness of the Manchester Chronic Obstructive Pulmonary Disease Fatigue Scale to pulmonary rehabilitation - Abebaw Mengistu Yohannes; Sheila Dryden; Nicola Alexander Hanania (SAGE Publishing, 2019)
Background: We examined the responsiveness of the Manchester Chronic Obstructive Pulmonary Disease (COPD) Fatigue Scale (MCFS) in patients with COPD following 8 weeks of pulmonary rehabilitation (PR). Methods: Patients ( n  = 273) with clinically stable COPD completed 8 weeks of outpatient multidisciplinary PR, comprising 2 h (1 h exercise and 1 h education) weekly. Anxiety, exercise capacity, quality of life, dyspnea, fatigue were measured pre- and post-PR, utilizing the Anxiety Inventory for Respiratory Disease (AIR), Incremental Shuttle Walk Test (ISWT), St. George's Respiratory Questionnaire (SGRQ), and modified Medical Research Council (mMRC) scale and MCFS, respectively. Results: The mean (SD) age of participants was 72 (8) years, and 50% were women. Total MCFS score fell after PR mean (95% confidence interval) −4.89 (-7.90 to −3.79) as did domain scores: physical −1.89 (-2.33 to −1.46), cognition −1.37 (-1.65 to −1.09), and psychosocial −1.62 (-2.00 to −1.62). Total MCFS effect size (ES) was 0.55; and for domains, physical was 0.52, cognition was 0.59, and psychosocial was 0.51. The ES for AIR was 0.30, mMRC was 0.38, SGRQ was 0.66, and ISWT was 1.19. MCFS changes correlated with changes in both SGRQ ( p  < 0.002) and AIR ( p  < 0.004), but not ISWT ( p  = 0.30) or mMRC ( p  = 0.18). The AIR, SGRQ, mMRC, and ISWT all improved after PR (all, p  < 0.001). Conclusion: The MCFS scale is a valid and responsive scale to measure fatigue in patients with COPD after pulmonary rehabilitation.